Eye movement control and its disorders - Atchareeya Wiwatwongwana (2018)
We review the supranuclear control centers and pathways leading to individual cranial nerve nuclei in the brainstem. We discuss horizontal and vertical gaze and their abnormalities, and review the cranial nerves which subserve eye movements, III, IV, VI, including their clinical testing. We highlight the sites at which these nerves are clinically affected, which often result in characteristic associated features with neurological localizing value. Differential diagnoses of cranial nerve palsies including Duane and Möbius syndromes are also described. Lastly, we discuss the nature of childhood neuromuscular junction disorders such as myasthenia gravis, as well as disorders of the muscle itself (chronic progressive external ophthalmoplegia (CPEO), thyroid orbitopathy). © 2013 Elsevier B.V.